2022
DOI: 10.3389/fpsyg.2022.936639
|View full text |Cite
|
Sign up to set email alerts
|

Patients With Severe Alcohol-Related Cognitive Impairment Improve in Flexibility When Abstinence Is Maintained: A Comparative Study With Alzheimer’s Disease

Abstract: The disease progression of severe alcohol-related cognitive impairment (ARCI) is debated. The aim of this study was to compare the cognitive change of patients with severe ARCI in inpatient setting to that of patients with Alzheimer’s disease (AD). Fifteen consecutive patients with severe ARCI were recruited between 2013 and 2015. They received inpatient detoxification, neurological assessment, and inpatient cognitive rehabilitation in specialized facilities. Twelve patients, with documented AD matched on sex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“… 123 Indeed, in a longitudinal study, people with alcohol-related dementia with monitored abstinence showed improved performance on executive functioning tests, whereas people with Alzheimer’s disease performed worse on memory tests over the same time spans. 124 The amount of alcohol consumed was unrelated to cognitive performance in patients with DSM-III –defined “primary degenerative dementia.” 125 In a more recent study of people diagnosed with MCI ( ICD-10 code F067) and evaluated by structured interview for alcohol use—i.e., low (less than 1 drink/week), moderate (1 to 14 drinks/week for men and 1 to 9 drinks/week for women), or heavy (more than 14 drinks/week for men and more than 9 drinks/week for women)—levels of alcohol consumed had no effect on MMSE scores; however, MMSE scores are notoriously insensitive to AUD-related cognitive decline. 126 , 127 …”
Section: Results Of the Reviewed Studiesmentioning
confidence: 99%
“… 123 Indeed, in a longitudinal study, people with alcohol-related dementia with monitored abstinence showed improved performance on executive functioning tests, whereas people with Alzheimer’s disease performed worse on memory tests over the same time spans. 124 The amount of alcohol consumed was unrelated to cognitive performance in patients with DSM-III –defined “primary degenerative dementia.” 125 In a more recent study of people diagnosed with MCI ( ICD-10 code F067) and evaluated by structured interview for alcohol use—i.e., low (less than 1 drink/week), moderate (1 to 14 drinks/week for men and 1 to 9 drinks/week for women), or heavy (more than 14 drinks/week for men and more than 9 drinks/week for women)—levels of alcohol consumed had no effect on MMSE scores; however, MMSE scores are notoriously insensitive to AUD-related cognitive decline. 126 , 127 …”
Section: Results Of the Reviewed Studiesmentioning
confidence: 99%
“…While some authors claim full recovery of cognitive functioning in AUD within a year of sobriety, see for example [57], others argue that cognitive impairments can persist well beyond a year of alcohol abstinence. In particular, EF may take longer to recover, with improvements reported up to six years of abstinence [11,12,58]. Second, the current study used a cross-sectional design to identify EF performances in KS, ARCI and controls.…”
Section: Discussionmentioning
confidence: 98%